2022
DOI: 10.3389/fsurg.2022.912024
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of deltoid ligament repair versus syndesmotic fixation in lateral malleolus fracture combined with both deltoid ligament injury and inferior tibiofibular syndesmotic disruption

Abstract: BackgroundTo compare clinical outcomes of deltoid ligament repair versus syndesmotic fixation in lateral malleolus fracture combined with both deltoid ligament injury and inferior tibiofibular syndesmotic disruption.MethodsPatients diagnosed with lateral malleolus fracture combined with both deltoid ligament injury and inferior tibiofibular syndesmotic disruption who received open reduction and internal fixation (ORIF) were retrospectively reviewed. Seventy-nine patients were enrolled into the study, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Although recent studies showed no differences in long term functional outcomes when the deltoid ligament was repaired (13), the deltoid ligament repair may lead to better ankle stability (11,14). Thus, more and more researchers believe that surgical repair of deltoid ligament rupture is the first choice to maintain the stability of ankle joint and prevent the occurrence of valgus and extransion of talus and long-term traumatic arthritis (15)(16)(17). In the present study, good functional outcomes were achieved and technique safety was observed based on the results of AOFAS, VAS, and ankle ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies showed no differences in long term functional outcomes when the deltoid ligament was repaired (13), the deltoid ligament repair may lead to better ankle stability (11,14). Thus, more and more researchers believe that surgical repair of deltoid ligament rupture is the first choice to maintain the stability of ankle joint and prevent the occurrence of valgus and extransion of talus and long-term traumatic arthritis (15)(16)(17). In the present study, good functional outcomes were achieved and technique safety was observed based on the results of AOFAS, VAS, and ankle ROM.…”
Section: Discussionmentioning
confidence: 99%